Evaluation of the effectiveness of adding androgen deprivation to modern dose‐escalated radiotherapy for men with favorable intermediate‐risk prostate cancer. Issue 15 (18th May 2016) - Falchook, Aaron D.; Basak, Ramsankar; Mohiuddin, Jahan J.; Chen, Ronald C.
Abstract : BACKGROUND: Randomized trials have shown that androgen‐deprivation therapy (ADT) improves survival for men with intermediate‐risk prostate cancer treated with radiotherapy (RT). The benefit of ADT to patients with favorable intermediate‐risk prostate cancer treated with modern dose‐escalated RT is unknown. This study evaluated the effectiveness of ADT on survival of men with favorable intermediate‐risk prostate cancer treated with dose‐escalated RT. METHODS: This study was a retrospective cohort analysis of men with favorable intermediate‐risk prostate cancer from 2004 to 2007 in the National Cancer Data Base. Favorable intermediate‐risk disease was defined as 1 adverse risk factor (prostate‐specific antigen level of 10‐20 ng/mL or Gleason score of 7) and clinical T1/T2 prostate cancer. All patients were treated with primary dose‐escalated RT (≥75.6 Gy or RT with a brachytherapy boost). Overall survival was analyzed with propensity score adjustment and Cox multivariate modeling. RESULTS: The study included 18, 598 patients. The use of ADT decreased from 43.5% in 2004 to 39.5% in 2007. The propensity score–adjusted survival analysis demonstrated similar 8‐year overall survival for men treated with dose‐escalated RT and ADT and men treated with RT alone (77.7% vs 78.4%). ADT was not associated with improved survival in any age or comorbidity subgroup. In a sensitivity analysis using Cox multivariate modeling, the receipt of ADT was not associated with overall survival (hazard ratio, 0.99; 95% confidence interval, 0.91‐1.07; P = .768). CONCLUSIONS: Adding ADT to modern dose‐escalated RT was not associated with improved survival for patients with favorable intermediate‐risk prostate cancer. The applicability of the survival benefit seen in older trials to modern patients is unclear. Because of the morbidity associated with ADT, dose‐escalated RT alone for patients with favorable intermediate‐risk prostate cancer may be a reasonable option. Cancer 2016;122:2341–2349 . © 2016 American Cancer Society . Abstract : Among patients with favorable intermediate‐risk prostate cancer, there are no differences in overall survival for men who receive androgen‐deprivation therapy with dose‐escalated radiotherapy and men who receive dose‐escalated radiotherapy alone; these findings remain after stratification by age and comorbidity. Dose‐escalated radiotherapy alone without androgen‐deprivation therapy may be an appropriate treatment for men with favorable intermediate‐risk prostate cancer. See also pages 2296‐8.